Murtad (Pindah Agama) dalam Kajian Hukum Islam - Abdul Muthalib (Sekolah Tinggi Agama Islam Sumatera Medan, 2020)
The jurists agree that a person who refuses the commandments of Allah and his Messenger means that he has returned (left) from Islam, whether because of doubt, refusal or disobedience. Allah SWT very clearly and firmly states that for apostates it means that he has wasted his good deeds and a person who dies in an apostate or disbelieving state is eternal in hell. A person is considered to have left Islam (Murtad) if he refuses an act which is required by religion by denying this obligation and considers it permissible to not fulfill it. For example, he does not perform prayers, zakat or hajj because he believes these things are not obligatory and he refuses to carry out his obligations. A person is also considered to have left Islam if he does not want to do what is required by Islamic law and the scholars agree on this obligation. a person is considered an infidel if he is reluctant or refuses to carry out an obligation even though he must know that obligation.